The coping process and acceptance among women with cervical cancer - Ummu Kulsum; Dwi Izzati; Eighty Mardiyan Kurniawati; Sulistiawati Sulistiawati (Majalah Obstetri & Ginekologi, 2022)
HIGHLIGHTS 1. One aspect of holistic care to women with cervical cancer is how they are able to cope with their disease.2. Coping process among women with cervical cancer was explored qualitatively.3. Social support, hobbies, and spirituality were found to have influence on coping and acceptance of the condition.   ABSTRACT Objective: To explore how the process of coping among women with cervical cancer. Materials and Methods: This study used a qualitative method with phenomenological design. Data were obtained through in-depth interviews. The sampling technique used was purposive sampling. Seven participants were selected according to the inclusion and exclusion criteria. Data analysis techniques used were transcribing verbatim data, data coding, categorizing, developing thematic contexts, and interpreting data. Results: The results of this study revealed that social support, hobbies, and spirituality helped women to cope with their illnesses. The results of this study have implications for health care providers to provide holistic care to women with cervical cancer. Conclusion: The process of coping and acceptance of the condition was different among women with cervical cancer, which was influenced by social support, hobbies, and spirituality.